Peran Gereja dalam Penguatan Karakter Remaja di Era Digital - Heryanto, Heryanto; Priandana, Daniel; Tambunan, Ryna Heppy (STTI Harvest Semarang, 2024)
Adolescence represents a transitional phase between childhood and adulthood. Adolescence is a period during which adolescents are particularly susceptible to a range of issues. The contemporary adolescent experience is characterised by a range of challenges, including substance abuse, violence, premarital sexual activity and bullying. Furthermore, the advent of digital technology has facilitated the influx of a plethora of unfiltered information into the lives of adolescents. It is imperative that adolescents receive guidance to enable them to withstand the influence of unhealthy social interactions. The objective of this research is to ascertain the role of the church in fostering the moral development of adolescents in the context of the digital age. The research employs a qualitative descriptive methodology, utilising a literature review from a range of sources, including academic journals and books. The findings of this research demonstrate that Christian teenagers in the digital age live in a context that prioritises mobility and the use of digital media devices, such as smartphones, to meet the needs of teenagers. The results indicate that the church plays a pivotal role in strengthening the character of teenagers. The church can utilise digital technology devices to enhance the character of teenagers through gadgets and the utilisation of web-based discipleship applications. AbstrakMasa remaja adalah masa peralihan dari masa kanak-kanak menuju dewasa. Masa remaja merupakan masa yang rawan terhadap berbagai masalah. Masalah masa remaja saat ini berkaitan dengan penggunaan narkoba, kekerasan, hubungan sex di luar nikah dan pembulian. Hal ini makin didorong oleh perkembangan teknologi digital sehingga masuknya berbagai informasi tanpa difilter dalam kehidupan para remaja. Penguatan karakter dibutuhkan agar remaja tidak mudah dipengaruhi oleh pergaulan yang tidak sehat. Penelitian ini bertujuan untuk menemukan peran gereja dalam penguatan karakter remaja di era digital. Penelitian ini menggunakan metode deskriptif kualitatif melalui studi pustaka atau literatur lewat berbagai sumber baik jurnal dan buku. Hasil penelitian menunjukkan kaum remaja Kristen di era digitalisasi hidup di dalam masa yang mengedepankan pergerakan dengan penggunaan perangkat media digital seperti ponsel pintar untuk menjawab kebutuhan remaja. Hasil penelitian menunjukkan bahwa gereja mempunyai peran yang besar dalam penguatan karakter remaja. Dalam hal ini, Gereja dapat menggunakan perangkat teknologi digital dalam melakukan penguatan karakter remaja melalui gadget, penggunaan aplikasi pemuridan berbasis web.